( 3 2 ) 6 × ( 3 4 ÷ 3 2 ) = 3 x
Solve for x without using a calculator.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Due to exponent laws, ( 3 2 ) 6 × ( 3 4 ÷ 3 2 ) is the same as 3 2 × 6 × 3 4 − 2 which equals 3 1 2 + 2 which equals 3 1 4
Therefore, x is 14.
Using a calculator it is obvious that the answer is 14
(3 2 ) 6 = 3 2 × 6 = 3 1 2 .
3 2 3 4 = 3 4 − 2 = 3 2 .
Now , 3 1 2 × 3 2 = 3 1 2 + 2 = 3 1 4 □.
∴ the answet is 3 1 4 .
Problem Loading...
Note Loading...
Set Loading...
3 x ⟹ x = ( 3 2 ) 6 × ( 3 4 ÷ 3 2 ) = 3 2 × 6 3 4 3 − 2 = 3 1 2 + 4 − 2 = 3 1 4 = 1 4